Ethics and organizational leadership : developing a normative model - Fryer, Mick (Oxford University Press, 2011)
By connecting theories of leadership and business ethics with moral philosophy and empirical research, this book sets out to develop an understanding of what comprises ethical leadership and to envisage a practicable model for contemporary organ